1998
DOI: 10.3171/jns.1998.89.6.0983
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol intoxication in a model of traumatic brain injury with hemorrhagic shock: effects on early physiological response

Abstract: In this model of TBI, acute EtOH intoxication in the presence of HS potentiates the physiological and metabolic alterations that may contribute to secondary brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 62 publications
(47 reference statements)
1
24
1
3
Order By: Relevance
“…Another possibility is that alcohol may impact hemodynamic and respiratory brainstem control centers accentuating acidosis through longer posttraumatic apnea periods, decreased ventilation, and impaired ventilatory responses, subsequently leading to decreased cerebral perfusion pressure and lower post-injury regional cerebral blood flow for hours post-injury (McQueen and Posey, 1975;Zink et al, 1993Zink et al, , 1995Zink et al, , 1998Zink et al, , 1999. A third mechanism implicates alcohol as a factor in facilitating WILDE ET AL.…”
Section: Interactive Effects Of Alcohol and Tbi Hypothesismentioning
confidence: 97%
“…Another possibility is that alcohol may impact hemodynamic and respiratory brainstem control centers accentuating acidosis through longer posttraumatic apnea periods, decreased ventilation, and impaired ventilatory responses, subsequently leading to decreased cerebral perfusion pressure and lower post-injury regional cerebral blood flow for hours post-injury (McQueen and Posey, 1975;Zink et al, 1993Zink et al, , 1995Zink et al, , 1998Zink et al, , 1999. A third mechanism implicates alcohol as a factor in facilitating WILDE ET AL.…”
Section: Interactive Effects Of Alcohol and Tbi Hypothesismentioning
confidence: 97%
“…Instead, significant hypotension, prolonged apnea, and increased mortality have been reported (Shapira et al, 1997;Yamakami et al, 1995;Zink and Feustel, 1995;Zink et al, 1993Zink et al, , 1998. Similarly, in a rat spinal cord 24, and 72 h).…”
mentioning
confidence: 89%
“…The instrumentation procedure has been previously described in detail (Zink et al, 1998(Zink et al, , 1999. Immature swine (20 kg) were sedated with ketamine, intubated, and anesthetized with isoflurane (1.15%) at an F I O 2 of 0.28.…”
Section: Instrumentationmentioning
confidence: 99%
“…In previous studies from our laboratory, which utilized a porcine fluid percussion model, we found early respiratory depression, decreased cerebral perfusion pressure (CPP), and decreased cerebral blood flow (CBF) in ethanol-treated animals (Zink and Feustel, 1995;Zink et al, 1993). When TBI is accompanied by hemorrhage, the deleterious effects of ethanol are magnified (Zink et al, 1998(Zink et al, , 1999.…”
mentioning
confidence: 92%